Formulation of Mouthwash Preparations Ethanol Extract of Coffee Beans Roasted Robusta (Coffea canephora) and Effectiveness Test on Bacteria Streptococcus mutans - Syaifur Rahman; Reni Ariastuti; Ahwan Ahwan (Journal of Nutraceuticals and Herbal Medicine, 2021)
Dental caries can be caused by Streptococcus mutans bacteria. Robusta coffee bean extract has an inhibitory effect on the growth of Streptococcus mutans bacteria. Compounds that have antibacterial activity are chlorogenic acid (CGA), caffeine, caffeic acid and trigonelline. Robusta coffee bean extract has the potential to be formulated into mouthwash. This study aims to make a mouthwash formula with the active ingredient of roasted Robusta coffee extract and then evaluate the preparation and test its effectiveness against S. mutans bacteria. Mouthwash preparations were made in 3 formulas with different glycerin concentrations, namely 5%, 10%, and 15%. The stability test of the preparation used the treatment before and after the forced condition. Bacterial inhibition test using agar diffusion method with the positive control, namely commercial mouthwash Chlorhexidine and negative control mouthwash formula without extract content. Data analysis used the Kruskal-Wallis test to determine the differences in each treatment, and the Mann-Whitney test to see which treatment groups were significantly different. The results of the evaluation of the stability of the preparation showed that the three formulations of the mouthwash of roasted Robusta coffee bean extract had organoleptic stability, pH, and viscosity. The results of the inhibitory effectiveness test showed that the mouthwash formulation of formula 1 produced an inhibition zone of 1.6 mm, formula 2 of 2.1 mm, formula 3 of 2.4 mm, positive control of 6.8 mm, and negative control did not produce obstacles zone. It can be concluded that the three mouthwash formulas have antibacterial activity in the weak category (5 mm). The concentration of glycerin in the formula had no significant effect on the stability of the preparation and the antibacterial effectiveness of S. mutans. The results of the inhibitory effectiveness test showed that the mouthwash formulation of formula 1 produced an inhibition zone of 1.6 mm, formula 2 of 2.1 mm, formula 3 of 2.4 mm, positive control of 6.8 mm, and negative control did not produce obstacles zone. It can be concluded that the three mouthwash formulas have antibacterial activity in the weak category (5 mm). The concentration of glycerin in the formula had no significant effect on the stability of the preparation and the antibacterial effectiveness of S. mutans. The results of the inhibitory effectiveness test showed that the mouthwash formulation of formula 1 produced an inhibition zone of 1.6 mm, formula 2 of 2.1 mm, formula 3 of 2.4 mm, positive control of 6.8 mm, and negative control did not produce obstacles zone. It can be concluded that the three mouthwash formulas have antibacterial activity in the weak category (5 mm). The concentration of glycerin in the formula had no significant effect on the stability of the preparation and the antibacterial effectiveness of S. mutans.